1996
DOI: 10.1007/bf00193938
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage inflammatory protein-1 alpha expression in non-neoplastic and neoplastic lung tissue

Abstract: The chemokines are members of a bipartite superfamily of soluble proteins that have been implicated in a wide range of acute and chronic inflammatory processes, as well as other immunoregulatory functions. Macrophage inflammatory protein-1 alpha (MIP-1alpha) belongs to the C-C subfamily of these chemokines and is primarily a potent chemoattractant and activator of monocytes. MIP-1alpha is also thought to play a role in host defence. We examined the expression of MIP-1-alpha in normal lung, inflammatory lung ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Fibroblast cells have been demonstrated to take part in the inflammatory reaction in psoriasis (Glowacka et al, 2010;Schirmer et al, 2010). Although not typical immune cells, fibroblast cells have been demonstrated to express FOXP3 and immune cytokines/receptors, including CCL3 and CCR5, upon stimulation (Konishi et al, 1996;Maurer and von Stebut, 2004;Zhu Shen et al, submitted). However, it is a fact that there should be some differences between these two cell types according to differences in their structures.…”
Section: Discussionmentioning
confidence: 95%
“…Fibroblast cells have been demonstrated to take part in the inflammatory reaction in psoriasis (Glowacka et al, 2010;Schirmer et al, 2010). Although not typical immune cells, fibroblast cells have been demonstrated to express FOXP3 and immune cytokines/receptors, including CCL3 and CCR5, upon stimulation (Konishi et al, 1996;Maurer and von Stebut, 2004;Zhu Shen et al, submitted). However, it is a fact that there should be some differences between these two cell types according to differences in their structures.…”
Section: Discussionmentioning
confidence: 95%
“…The previous study demonstrated that overexpression of RANTES was associated with improved prognosis in lung cancer [ 28 ]. Lung cancer cells were found to produce MIP-1α which might affect the interaction between lung cancer and host inflammatory cells [ 29 ]. The present study observed that mRNA expressions of RANTES and MIP-1α in cancer cells after co-culture of cancer cells and PBMCs in a concentration-dependent pattern, accompanied with the up-regulation of Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…Although to our knowledge there are no reports to date regarding the production of chemokines by colorectal carcinoma, lung carcinoma was reported to produce macrophage inflammatory protein-1␣, 28 a C-C chemokine that is a potent chemoattractant and activator of monocytes. 29 Even if macrophages are recruited to the tumor stroma, it does not necessarily mean that they are in an active form.…”
mentioning
confidence: 99%